Tingkat Depresi dan Kualitas Hidup Penderita HIV/AIDS di Kelompok Dukungan Sebaya Gajah Mungkur Wonogiri - Marni Marni; Nita Yunianti Ratnasari; Domingos Soares; Putri Halimu Husna (FORIKES, 2020)
HIV / AIDS sufferers overcome various problems both physical, social, and emotional. If emotional problems such as decreased arousal succeed, stress, confusion, depression, are not immediately addressed then it can reduce the quality of life of people with HIV / AIDS. The purpose of this study was to determine the relationship of depression levels with the quality of life of people with HIV / AIDS in the Gajah Mungkur Wonogiri Peer Support Group. The study used descriptive correlative with a cross sectional study design. The sample took with a consecutive sampling, with the sample size of 116 respondents. There were 14 respondents did not arrive when the data was taken. The instruments in this study used the Beck Depression Inventory (BDI) and WHOQOLHIV-BREF questionnaire. Data were analyzed using Chi-Square test. This study result showed that depression level of respondent were 25 respondents did not experience depression, 21 respondents (18.1%) had good perception quality, the remaining 4 respondents had poor quality of life, while 36 respondents experienced an increase in poor quality of life as many as 19 respondents (16.4%). Respondents who experience severe depression as many as 33 respondents (28.4%) more have a poor quality of life as many as 20 respondents (17.2%). The result showed that p-value = 0.001, which means there was a relationship between the level of depression with the quality of life of people with HIV / AIDS in the Gajah Mungkur Peer Support Group. Keywords: depression; HIV / AIDS; quality of life ABSTRAK Penderita HIV/AIDS mengalami berbagai masalah baik fisik, sosial, maupun emosional. Apabila masalah emosional seperti penurunan gairah bekerja, stress, bingung, malu, depresi tidak segera diatasi maka bisa menurunkan kualitas hidup penderita HIV/AIDS. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat depresi dengan kualitas hidup penderita HIV/AIDS di Kelompok Dukungan Sebaya Gajah Mungkur Wonogiri. Jenis penelitian ini adalah deskriptif korelatif dengan desain cross sectional study melalui kuesioner, Teknik pengambilan sampling dengan consecutive sampling dengan ukuran sampel sebanyak 116 responden. Instrumen pada penelitian ini adalah kuesioner Beck Depression Inventory (BDI) dan WHOQOLHIV-BREF. Analisis data dilakukan menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa 25 responden tidak mengalami depresi, 21 responden (18,1%) memiliki persepsi kualitas hidupnya baik, sisanya 4 responden memiliki kualitas hidup yang buruk; sedangkan 36 responden mengalami depresi sedang memiliki kualitas hidup yang buruk sebanyak 19 responden (16,4%). Responden yang mengalami depresi berat sebanyak 33 responden (28,4%) lebih banyak memiliki kualitas hidup yang buruk sejumlah 20 responden (17,2%). Nilai p adalah 0,001, yang berarti ada hubungan antara tingkat depresi dengan kualitas hidup penderita HIV/AIDS di Kelompok Dukungan Sebaya Gajah Mungkur Wonogiri. Kata kunci: depresi; HIV/AIDS; kualitas hidup